Structure and form in design : critical ideas for creative practice - Hann, M. A. (London ; New York : Berg, 2012)
This book provides a critical examination of structure and form in design, covering a range of topics of great value to students and practitioners engaged in any of the specialist decorative arts and design disciplines. The complexities of two-dimensional phenomena are explained and illustrated in detail, while various three-dimensional forms are also discussed. In the context of the decorative arts and design, structure is the underlying framework, and form the resultant, visible, two- or three-dimensional outcome of the creative process. Whether hidden or visually detectable in the final design, structure invariably determines whether or not a design is successful in terms of both its aesthetics and its practical performance. Hann successfully identifies various geometric concepts, and presents and discusses a number of simple guidelines to assist the creative endeavours of both accomplished and student practitioners, teachers and researchers.
Introduction -- The fundamentals and their role in design -- Underneath it all -- Tiling the plane without gap or overlap -- Symmetry, patterns and fractals -- The stepping stone of Fibonacci and the harmony of a line divided -- Polyhedra, spheres and domes -- Structures and form in three dimensions -- Variations on a theme: modularity, closest packing and partitioning -- Structural analysis in the decorative arts, design and architecture -- A designer's framework.
Includes bibliographical references (p. [171]-176) and index.
Keywords: Design -- Methodology; Design -- Philosophy